2015
DOI: 10.1002/pbc.25777
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Extra‐Renal Noncerebral Rhabdoid Tumors with VIDE

Abstract: Extra-renal noncerebral rhabdoid tumors (ERRTs) are highly aggressive and often lethal. An optimal chemotherapy regimen for ERRT remains undetermined. We report on three pediatric patients successfully treated with vincristine, ifosfamide, doxorubicin, and etoposide (VIDE). Two of our patients who had metastatic or refractory disease have survived more than 2 years, one disease free without myeloablative megatherapy. The treatment with high-dose alkylator therapy is reported to have a beneficial effect on surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Naoko Yasui et al reported that after using VIDE (vincristine, ifosfamide, neomycin and etoposide) regimen in three MERT patients, both primary and metastatic lesions were effectively reduced and disappeared, and the patients received a better prognosis. [20] The results suggest that adjuvant chemotherapy has a positive significance in improving the prognosis. However, Adam D. Wolfe et al have reported two patients with neck MRT who have no evidence of disease at seven and four years from diagnosis, following aggressive multimodal alkylator-based chemotherapy, local control with XRT, and consolidative high dose chemotherapy with autologous stem cell rescue (HDC-ASCR) using CEM conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naoko Yasui et al reported that after using VIDE (vincristine, ifosfamide, neomycin and etoposide) regimen in three MERT patients, both primary and metastatic lesions were effectively reduced and disappeared, and the patients received a better prognosis. [20] The results suggest that adjuvant chemotherapy has a positive significance in improving the prognosis. However, Adam D. Wolfe et al have reported two patients with neck MRT who have no evidence of disease at seven and four years from diagnosis, following aggressive multimodal alkylator-based chemotherapy, local control with XRT, and consolidative high dose chemotherapy with autologous stem cell rescue (HDC-ASCR) using CEM conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Naoko Yasui et al reported a case in which the lesion was improved by radiotherapy before surgery and then recurred, causing the disease to worsen. [20] Chemotherapy and surgery were still used to control the lesion and obtain the opportunity for surgery. According to the literature, VIDE chemotherapy regimen has some potential benefits for the survival of patients, but more reports and studies are needed to confirm it.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current curative effect of radiotherapy is not exact. Yasui et al reported a case in which the lesion was improved by preoperative radiotherapy and then relapsed resulting in exacerbation of the disease 27 …”
Section: Discussionmentioning
confidence: 99%
“…Rhabdoid tumors (RT) are rare and more aggressive malignancies that predominantly occur in infants and young children [ 1 ]. Depending on the anatomical localization, the 3 primary localizations of RT are atypical teratoid/rhabdoid tumor (AT/RT), extra-renal non-cranial rhabdoid tumor, and malignant rhabdoid tumor of the kidney (MRTC) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%